DIVORCE AS RISK FACTOR FOR CHILDREN’S PERCEPTION OF PARENTAL REJECTION (Annual of the Faculty of Philosophy in Skopje, 2021)
The aim of this study was to investigate whether divorce is a risk factor for children’s perception of parental rejection. The sample included 96 participants in total, of which 33 children whose parents are divorced and 62 whose parents are married. Children in both groups did not differ significantly regarding age or gender (age range: 6-17 years, Mdiv =11±2.9 years, Mmarr =12±2.2 years, approximately 65% were female in both groups). The Child PARQ short form was used to assess perceptions of parental acceptance/rejection. Higher test scores indicate greater rejection by parents. The findings show that children’s age was significantly correlated with the perception of maternal rejection only in the group of divorced parents (r = .44, p < .05). A two-way ANOVA was conducted that examined the effect of gender and family type on PARQ scores. It was found that only the main effect of family type was significant, regardless of the child’s sex (F (1,95) = 204.537, p < .001). Children of divorced parents assessed both parents as rejecting (Mm = 79.4 ± 16.5; Mf = 77.1 ± 14.8), while children of married parents assessed them as accepting (Mm = 36.8 ± 11.9; Mf = 38.4 ± 12.5). Further on, PARQ scores for mother and father respectively were positively correlated in the group of married parents (r = .56, p < .01), while no significant association was found in the group of divorced parents. Partial η2 = .69 indicates a large effect and confirms that divorce is a significant risk factor of children’s perception of parental rejection.
Keywords: perceived parental rejection; child; married parents; divorced parents